Association between Insulin-Like Growth Factor Binding Protein-7 and Heart Failure - Ghasempour, Parisa; Khanmohammadi, Shaghayegh; Rezaei, Nima (Current Medicinal Chemistry, 2025)
Heart failure (HF), a widespread public health issue, affects about 26 million people all around the world, and its incidence and prevalence are still growing. Measuring serum biomarkers is beneficial in diagnosing HF and evaluating its prognosis. During the previous decade, various investigations have focused on identifying new HF biological markers that would have additional and/or superior prognostic, diagnostic, or classification value. While heart-specific biological markers, such as atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP), are commonly applied in clinical practice, there is still an unmet need for new markers in HF management. Insulin-like growth factor-binding protein-7 (IGFBP7), a cellular senescence marker, has been considered as a candidate biomarker in HF. This study aims to comprehensively reveal the underlying mechanism connecting IGFBP-7 to HF and review studies evaluating the prognostic or diagnostic performance of IGFBP-7 in combination with or in contrast with other potential HF biological markers. Increased IGFBP7 levels are associated with a set of functional and structural heart abnormalities such as diastolic dysfunction. Increased IGFBP7 concentrations seem to be an indicator of cardiac overload or injury and are related to HF major risk factors, including atherosclerosis, diabetes, and renal function. IGFBP7 is predictive of short and long-term outcomes in the HF population and can independently predict the rate of hospitalization and HF-related mortality.
Keywords: senescence marker